The Effect of PhET Virtual Laboratory Implementation on Students’ Higher Order Thinking Skills - Rahmiati Darwis; Muhammad Rizal Hardiansyah (Postgraduate, University of Mataram, 2023)
This study aimed to know the effect of using PhET virtual laboratory towards students’ higher order thinking skills on linear motion. This research is quasy experimental research that uses the static group pretest-posttest design. The population of this research is all grade VIII students of MTsN mbon in the academic year 2021/2022 and the sample of this research is grade VIII4 as experimental group and VIII5 as control group that determined by simple random sampling technique. The instrument that used to collect the data is test HOTs that made in terms of multiple choices test. The data is analyzed by statistical formula of N-gain and t-test by SPSS 26. The result of N-gain of experimental group HOTs is 0.40 and control group is 0.19. The result of t-test shows that tcount of HOTs is 7.762 ≥ ttable is 2.000. It means that there is a significant difference of HOTs of students on the linear motion. Therefore, it can be concluded that the use of virtual laboratorial PhET has positive effect towards high order thinking skill of students on the linear motion